High-Temperature-Resistant Diverting Acid for Carbonate Formation Fracturing in Sichuan Basin: A Property Evaluation and Field Study - Zhiheng Zhao; Chuan Sun; Yuzhou Liu (Geofluids)
The targeted carbonate formation in Gao-Mo Block located in the middle of Sichuan Basin becomes deeper with the progress of development, and it mainly exhibits high temperature and strong heterogeneity. Higher requirements for temperature resistance performance and acidizing effect of diverting acid are put forward. In this work, the high-temperature-resistant diverting acid (HTRDA) was employed to evaluate the compatibility, temperature resistance, friction reduction, and acidizing effectiveness based on formation characteristics, and it was applied to demonstrate its reliability and adaptability in field. The following study results are obtained. The HTRDA has good compatibility and its peak viscosity could reach 31 mPa·s at the temperature of 170°C. Compared with the friction of water, the friction reduction rate of HTRDA can reach 67.8%. And the permeability change of core with low permeability could be increased by 53.5-61% after acidification. Furthermore, during the acid fracturing of Well M, the maximum diverting pressure of HTRDA gets to 10 MPa and the friction reduction rate is about 66.5% that is consistent with the experimental data. The test production of Well M is 35.64×104 m3/d and the acid fracturing obtain a great result.